Mukjizat dalam al-qur’an: kajian tentang hakikat dan aspek-aspeknya - Karoma, Qoirotun (Maliki Interdisciplinary Journal, 2026)
This article discusses the concept of miracles in the Qur’an through an examination of their essence, forms, and relevance in modern life. This study is motivated by the importance of understanding miracles not merely as supernatural events, but as part of the divine message that carries theological and moral significance. The research employs a literature review method by analyzing Qur’anic verses, classical and contemporary exegesis, as well as relevant scholarly works. The findings indicate that miracles serve as proof of prophethood and a manifestation of Allah power, with diverse forms such as sensory, scientific, and linguistic miracles. Furthermore, miracles remain relevant in contemporary life as they strengthen faith amidst scientific advancement, provide moral inspiration, and offer a spiritual perspective needed by modern society. Thus, miracles in the Qur’an do not only function as historical narratives, but also as a source of values and reflection in contemporary life.